2008
DOI: 10.1088/0268-1242/23/3/035005
|View full text |Cite
|
Sign up to set email alerts
|

Non-polara-plane ZnMgO1/ZnO quantum wells grown by molecular beam epitaxy

Abstract: Non-polar (Zn, Mg)O/ZnO quantum wells (QWs) have been grown on a r-plane sapphire by molecular beam epitaxy. The heterostructures are fully oriented and show a single wurtzite phase at least up to 40% Mg content, as evidenced by means of the x-ray pole figures analysis. The microstructure is dominated by stacking faults and related partial dislocations as shown by the transmission electron microscopy analysis. A series of QWs with different widths has then been studied, showing the absence of the quantum confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 30 publications
0
41
0
4
Order By: Relevance
“…7,8 Furthermore, it has been experimentally shown that the lack of internal electric field in a-plane ZnMgO/ZnO heterostructures results in more efficient radiative recombination in quantum wells, i.e., no quantum confined Stark effect, as desired for emitter applications. 9 Currently, work on Mg x Zn 1Àx O is in the very early stages in terms of applications of Mg x Zn 1Àx O for devices applications such as UV light emitting diodes (LEDs) and detectors. [3][4][5]10,11 Ultimately, as with all optoelectronic devices, the presence of various defects that can create bandgap states is of great interest since they reduce performance, hinder reliability, and lower device lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Furthermore, it has been experimentally shown that the lack of internal electric field in a-plane ZnMgO/ZnO heterostructures results in more efficient radiative recombination in quantum wells, i.e., no quantum confined Stark effect, as desired for emitter applications. 9 Currently, work on Mg x Zn 1Àx O is in the very early stages in terms of applications of Mg x Zn 1Àx O for devices applications such as UV light emitting diodes (LEDs) and detectors. [3][4][5]10,11 Ultimately, as with all optoelectronic devices, the presence of various defects that can create bandgap states is of great interest since they reduce performance, hinder reliability, and lower device lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many studies have reported that Mg is favorable for growth of ternary compounds with ZnO due to the similarity of ionic radius between Zn (0.60 Å) and Mg (0.57 Å) [13][14][15]. However, only a few studies on growth and properties of nonpolar Mg x Zn 1Àx O film have been performed [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, devices based on [0001]-oriented wurtzite materials are known to present spontaneous and piezoelectric electrostatic fields which spatially separate electrons and holes in the active layers and, thus, limit the device quantum efficiency [8]. Therefore, alternative growth orientations have been recently proposed with the polar [0001] direction within the growth plane [9,10] and quantum wells (QWs) free of electric fields have already been demonstrated [9][10][11].…”
Section: Introductionmentioning
confidence: 99%